Microbial Quality Assessment of Kunun Zaki Local Beverages Sold in Wukari Metropolis, Taraba State, Nigeria - Chidi, Obasi Blessing; Bulus, Gago Nasiha (African Journal of Sciences and Traditional Medicine, 2025)
Kunun-zaki is a traditional indigenous beverage widely consumed in Northern Nigeria, typically prepared from millet, guinea corn, or maize. Milky in appearance, kunun-zaki is rich in carbohydrates, vitamins, and minerals, but low in protein content, and is often consumed within a few hours of production. This study aimed to assess the microbial quality of kunun-zaki sold in Wukari metropolis to evaluate its safety for consumer intake. A total of 40 kunun-zaki samples were collected from vendors across four different clusters, with ten samples obtained from each zone. The samples were analyzed for microbial load using standard microbiological procedures. Results indicated total aerobic plate counts ranging from 9.8×10⁵ to 1.0×10⁵ cfu/ml in Zone A; 9.7×10⁵ to 1.21×10⁵ cfu/ml in Zone B; 9.7×10⁵ to 1.0×10⁵ cfu/ml in Zone C; and 4.96×10⁵ to 1.12×10⁵ cfu/ml in Zone D. Bacterial isolates identified across all zones included Staphylococcus spp. (24.6%), Escherichia coli (20.9%), Micrococcus (19.7%), Pseudomonas (9.2%), Salmonella spp. (7.4%), Bacillus spp. (6.17%), Klebsiella spp. (4.3%), Vibrio spp. (3.08%), and Enterobacter spp., which appeared in Zones A (2.4%) and D (4.87%). The high bacterial load and presence of pathogenic species indicate significant contamination, posing potential health risks to consumers. The study concludes with a call for stringent hygienic practices among producers and vendors during the preparation and storage of kunun-zaki to safeguard public health.